Measured performance of filtration and ventilation systems for fine and ultrafine particles and ozone in an unoccupied modern California house. (27th December 2016) - Singer, B. C.; Delp, W. W.; Black, D. R.; Walker, I. S.
Abstract: This study evaluated nine ventilation and filtration systems in an unoccupied 2006 house located 250 m downwind of the I‐80 freeway in Sacramento, California. Systems were evaluated for reducing indoor concentrations of outdoor particles in summer and fall/winter, ozone in summer, and particles from stir‐fry cooking. Air exchange rate was measured continuously. Energy use was estimated for year‐round operation in California. Exhaust ventilation without enhanced filtration provided indoor PM2.5 that was 70% lower than outdoors. Supply ventilation with MERV13 filtration provided slightly less protection, whereas supply MERV16 filtration reduced PM2.5 by 97‐98% relative to outdoors. Supply filtration systems used little energy but provided no benefits for indoor‐generated particles. Systems with MERV13‐16 filter in the recirculating heating and cooling unit (FAU) operating continuously or 20 min/h reduced PM2.5 by 93‐98%. Across all systems, removal percentages were higher for ultrafine particles and lower for black carbon, relative to PM2.5 . Indoor ozone was 3‐4% of outdoors for all systems except an electronic air cleaner that produced ozone. Filtration via the FAU or portable filtration units lowered PM2.5 by 25‐75% when operated over the hour following cooking. The energy for year‐round operation of FAU filtration with an efficient blower motor was estimated at 600 kWh/year.